2007
DOI: 10.1103/physrevlett.98.131102
|View full text |Cite
|
Sign up to set email alerts
|

Ising Analogue to Compact-Star Matter

Abstract: By constructing an Ising analogue of compact-star matter at sub-saturation density we explored the effect of Coulomb frustration on the nuclear liquid-gas phase transition. Our conclusions is twofold. First, the range of temperatures where inhomogeneous phases form expands with increasing Coulomb-field strength. Second, within the approximation of uniform electron distribution, the limiting point upon which the phase-coexistence region ends does not exhibit any critical behaviour. Possible astrophysics consequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Because of the very high electron incompressibility, the convexity observed in the baryonic part of the energy density is not present any more in the total thermodynamic potential. This is known in the literature as the quenching of the phase transition due to Coulomb frustration [84,85], and shows [86] that convexities in the (free) energy density do not necessarily correspond to instabilities in the physical system. This shows that if one wants to formulate the equilibrium problem in the grandcanonical ensemble, one has to account for the electron zero point motion.…”
Section: E Phase Transitions In the Inner Crust?mentioning
confidence: 99%
“…Because of the very high electron incompressibility, the convexity observed in the baryonic part of the energy density is not present any more in the total thermodynamic potential. This is known in the literature as the quenching of the phase transition due to Coulomb frustration [84,85], and shows [86] that convexities in the (free) energy density do not necessarily correspond to instabilities in the physical system. This shows that if one wants to formulate the equilibrium problem in the grandcanonical ensemble, one has to account for the electron zero point motion.…”
Section: E Phase Transitions In the Inner Crust?mentioning
confidence: 99%
“…In the crust of a neutron star the transition from the Wigner crystal phase to the quantum liquid also proceeds through a cluster phase as a function of density [8]. Clustering occurs as a transition between the quantum liquid and solid state phases because of frustration effects, that is, due to the interplay between an attractive and a repulsive interac-tion [9,10]. This is the case in the crust of neutron stars or for gelification in condensed matter.…”
mentioning
confidence: 99%
“…It has been argued in ref. [16] that this generic frustration effect should lead to a quenching of the first order phase transition. We have shown that the phase transition is observed in the grandcanonical ensemble.…”
Section: Grandcanonical Formulationmentioning
confidence: 96%